2004
DOI: 10.1093/humrep/deh107
|View full text |Cite
|
Sign up to set email alerts
|

History of induced abortion as a risk factor for preterm birth in European countries: results of the EUROPOP survey

Abstract: Identifying subgroups of preterm births on the basis of the complications involved in delivery increases our understanding of the mechanisms by which previous induced abortion affects subsequent pregnancy outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
53
1
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 34 publications
11
53
1
9
Order By: Relevance
“…The occurrence of two or more induced abortion was high in the age group of 25-34 years amounting to 62.2% in the study conducted by Henriet L and Kaminski (8) which was observed in our study with 97 (71.9%) women in the induced abortion group falling in the age group of 25-35 years. This was also consistent with study conducted by Ancel PY et al (11) reporting 83.6% of women with previous abortions falling in the 20-35 year age group. 63(46.7%) women in the induced abortion group were para one which was comparable with the results of Henriet L and Kaminski M (8) study who found 32.9% of the women to be para one.…”
Section: Discussionsupporting
confidence: 93%
“…The occurrence of two or more induced abortion was high in the age group of 25-34 years amounting to 62.2% in the study conducted by Henriet L and Kaminski (8) which was observed in our study with 97 (71.9%) women in the induced abortion group falling in the age group of 25-35 years. This was also consistent with study conducted by Ancel PY et al (11) reporting 83.6% of women with previous abortions falling in the 20-35 year age group. 63(46.7%) women in the induced abortion group were para one which was comparable with the results of Henriet L and Kaminski M (8) study who found 32.9% of the women to be para one.…”
Section: Discussionsupporting
confidence: 93%
“…Contrary to common belief, population-based studies [34][35][36] have found that elective pregnancy terminations in the first and second trimesters are associated with a very small but apparently real increase in the risk of subsequent spontaneous preterm birth (PTB). 37 The mechanism is unknown.…”
Section: Identification Of Women With a Prior Preterm Birthmentioning
confidence: 87%
“…Cases were classified according to the main obstetric complication leading to the preterm birth [18,19]; six mutually exclusive hierarchical groups were defined. The first major complication encountered (moving from group 1 to group 6) was retained, even if other complications lower down the list were also present.…”
Section: Populationmentioning
confidence: 99%